Functional rescue of mutant ABCA1 proteins by sodium 4-phenylbutyrate[S] - Brie Sorrenson; Rachel J. Suetani; Michael J.A. Williams; Vivienne M. Bickley; Peter M. George; Gregory T. Jones; Sally P.A. McCormick (Journal of Lipid Research, 2013)
Mutations in the ATP-binding cassette transporter A1 (ABCA1) are a major cause of decreased HDL cholesterol (HDL-C), which infers an increased risk of cardiovascular disease (CVD). Many ABCA1 mutants show impaired localization to the plasma membrane. The aim of this study was to investigate whether the chemical chaperone, sodium 4-phenylbutyrate (4-PBA) could improve cellular localization and function of ABCA1 mutants. Nine different ABCA1 mutants (p.A594T, p.I659V, p.R1068H, p.T1512M, p.Y1767D, p.N1800H, p.R2004K, p.A2028V, p.Q2239N) expressed in HEK293 cells, displaying different degrees of mislocalization to the plasma membrane and discrete impacts on cholesterol efflux, were subject to treatment with 4-PBA. Treatment restored localization to the plasma membrane and increased cholesterol efflux function for the majority of mutants. Treatment with 4-PBA also increased ABCA1 protein expression in all transfected cell lines. In fibroblast cells obtained from low HDL-C subjects expressing two of the ABCA1 mutants (p.R1068H and p.N1800H), 4-PBA increased cholesterol efflux without any increase in ABCA1 expression. Our study is the first to investigate the effect of the chemical chaperone, 4-PBA on ABCA1 and shows that it is capable of restoring plasma membrane localization and enhancing the cholesterol efflux function of mutant ABCA1s both in vitro and ex vivo. These results suggest 4-PBA may warrant further investigation as a potential therapy for increasing cholesterol efflux and HDL-C levels.